MULTIDISCIPLINARY AND PATIENT-PARENT BINOMIAL PERCEPTIONS OF PALLIATIVE CARE IN PEDIATRIC ONCOLOGY: AN INTEGRATIVE LITERATURE REVIEW (CIPEEX, 2022)
CHILDHOOD CANCER HAS GROWN EXPONENTIALLY WORLDWIDE. PATIENTS AND FAMILY MEMBERS AREVULNERABLE AND IN NEED OF PALLIATIVE CARE AND, IN VIEW OF THE NEED TO PROMOTE COMPREHENSIVEHEALTH CARE, IT IS IMPORTANT TO KNOW THE VIEWS OF THOSE WHO CARRY OUT AND THOSE WHO EXPERIENCETHIS PROPOSAL. THEREFORE, THE OBJECTIVE OF THIS INTEGRATIVE LITERATURE REVIEW WAS TO ANALYZE THEPERCEPTIONS OF THE MULTIDISCIPLINARY TEAM AND THE PATIENT-PARENT BINOMIAL REGARDING PALLIATIVECARE IN PEDIATRIC ONCOLOGY. AS A METHODOLOGY, A SEARCH WAS CARRIED OUT IN THE FOLLOWINGDATABASES: VIRTUAL HEALTH LIBRARY (BVS), GOOGLE SCHOLAR, CAPES PORTAL AND SCIELO (SCIENTIFICELECTRONIC LIBRARY ONLINE), USING THE DESCRIPTORS IN SCIENCE AND HEALTH (DECS) "PALLIATIVE CARE",€ŒONCOLOGY€ AND €ŒPEDIATRICS€. A TOTAL OF 20 ARTICLES PUBLISHED BETWEEN 2016 AND 2022 WERESELECTED. IN THIS CONTEXT, THE DIFFICULTY FACED BY PROFESSIONALS WAS HIGHLIGHTED, AS THEY NEEDED TOSEPARATE THE EMOTIONAL SIDE FROM THE PROFESSIONAL, BUT IN A WAY THAT HUMANITY WAS NOT LOST. IT ISALSO NOTED THE FRAGILITY OF THE PATIENT AND THOSE RESPONSIBLE FOR THEM WHEN THEY ARE FACED WITHSPECIALISTS WHO DEAL COLDLY WITH THE SITUATION, DUE TO ITS DAILY ROUTINE. IN THIS WAY, THE RELEVANCEOF A TRAINED AND HUMANIZED TEAM IS PERCEIVED, WHICH IS ABLE TO TREAT THE PATIENT AS A WHOLE, BUTWHICH ALSO RECEIVES SOCIO-EMOTIONAL SUPPORT, IN ORDER TO PRESERVE THEIR OWN MENTAL HEALTH, AND,IT IS PROVEN, THE BENEFITS PERCEIVED BY THE BINOMIAL PATIENT-PARENTS WHO ARE ASSISTED BY PALLIATIVECARE.
Keywords: contraceptivo hormonal; efeitos; saúde contraceptiva.